The use of patient-reported outcome measures to guide referral for hip and knee arthroplasty: part 1: the development of an evidence-based model linking preoperative score to the probability of gaining benefit from surgery. (July 2020) - Price, Andrew J.; Kang, Sujin; Cook, Jonathan A.; Dakin, Helen; Blom, Ashley; Arden, Nigel; Fitzpatrick, Ray; Beard, David J.; ,
Abstract : Aims: To calculate how the likelihood of obtaining measurable benefit from hip or knee arthroplasty varies with preoperative patient-reported scores. Methods: Existing UK data from 222, 933 knee and 209, 760 hip arthroplasty patients were used to model an individual's probability of gaining meaningful improvement after surgery based on their preoperative Oxford Knee or Hip Score (OKS/OHS). A clinically meaningful improvement after arthroplasty was defined as ≥ 8 point improvement in OHS, and ≥ 7 in OKS. Results: The upper preoperative score threshold, above which patients are unlikely to achieve any meaningful improvement from surgery, is 41 for knees and 40 for hips. At lower scores, the probability of improvement increased towards a maximum of 88% (knee) and 95% for (hips). Conclusion: By our definition of meaningful improvement, patients with preoperative scores above 41 (OKS) and 40 (OHS) should not be routinely referred to secondary care for possible arthroplasty. Using lower thresholds would incrementally increase the probability of meaningful benefit for those referred but will exclude some patients with potential to benefit. The findings are useful to support the complex shared decision-making process in primary care for referral to secondary care; and in secondary care for experienced clinicians counselling patients considering knee or hip arthroplasty, but should not be used in isolation. Cite this article: Bone Joint J 2020;102-B(7):941–949.